Alcohol flushing syndrome is significantly associated with intracranial aneurysm rupture in the Chinese Han population - Chen, Xiheng; Gui, Siming; Deng, Dingwei; Dong, Linggen; Zhang, Longhui; Wei, Dachao; Jiang, Jia; Ge, Huijian; Liu, Peng; Lv, Ming; Li, Youxiang (Frontiers in Neurology, 2023)
OBJECTIVE: Although alcohol flushing syndrome (AFS) has been associated with various diseases, its association with intracranial aneurysm rupture (IAR) is unclear. We aimed to examine this association in the Chinese Han population. METHODS：We retrospectively reviewed Chinese Han patients with intracranial aneurysms who were evaluated and treated at our institution between January 2020 and December 2021. AFS was determined using a semi-structured telephone interview. Clinical data and aneurysm characteristics were assessed. Univariate and multivariate logistic regression were conducted to determine independent factors associated with aneurysmal rupture. RESULTS: A total of 1170 patients with 1059 unruptured and 236 ruptured aneurysms were included. The incidence of habitual alcohol consumption and aneurysm rupture was significantly higher in patients without AFS (P <0.001). In the univariate analyses, AFS (odds ratio [OR] 0.49; 95% confidence interval [CI], 0.34–0.72) was significantly associated with IAR. In the multivariate analysis, AFS was an independent predictor of IAR (OR 0.50; 95%, CI, 0.35–0.71). Multivariate analysis revealed that AFS was an independent predictor of IAR in both habitual (OR 0.11; 95% CI, 0.03–0.45) and non-habitual drinkers (OR 0.69; 95% CI, 0.49–0.96). CONCLUSION: AFS may be a novel clinical marker to assess the risk of intracranial aneurysm rupture. The association between AFS and IAR exists independently of alcohol consumption. This implies that there may be a potential pathophysiological link between ADLH2 gene polymorphisms and the development and rupture of intracranial aneurysms. Further single nucleotide polymorphism testing and molecular biology studies are warranted.